The Tectonics and Active Faulting of Haiti from Seismicity and Tomography. Issue 3 (29th March 2019) - Possee, Daniel; Keir, Derek; Harmon, Nicholas; Rychert, Catherine; Rolandone, Frédérique; Leroy, Sylvie; Corbeau, Jordane; Stuart, Graham; Calais, Eric; Illsley‐Kemp, Finnigan; Boisson, Dominique; Momplaisir, Roberte; et al.
Abstract: Oblique convergence of the Caribbean and North American plates has partitioned strain across a major transpressional fault system that bisects the island of Hispaniola. The devastating MW 7.0, 2010 earthquake that struck southern Haiti, rupturing an unknown fault, highlighted our limited understanding of regional fault segmentation and its link to plate boundary deformation. Here we assess seismic activity and fault structures across Haiti using data from 33 broadband seismic stations deployed for 16 months. We use traveltime tomography to obtain relocated hypocenters and models of V p and V p /V s crustal structure. Earthquake locations reveal two clusters of seismic activity. The first corresponds to aftershocks of the 2010 earthquake and delineates faults associated with that rupture. The second cluster shows shallow activity north of Lake Enriquillo (Dominican Republic), interpreted to have occurred on a north‐dipping thrust fault. Crustal seismic velocities show a narrow low‐velocity region with an increased V p /V s ratio (1.80–1.85) dipping underneath the Massif de la Selle, which coincides with a southward‐dipping zone of hypocenters to a depth of 20 km beneath southern Haiti. Our observations of seismicity and crustal structure in southern Haiti suggests a transition in the Enriquillo fault system from a near vertical strike‐slip fault along the Southern Peninsula to a southward‐dipping oblique‐slip fault along the southern border of the Cul‐de‐Sac‐Enriquillo basin. This result, consistent with recent geodetic results but at odds with the classical seismotectonic interpretation of the Enriquillo fault system, is an important constraint in our understanding of regional seismic hazard. Key Points: Local earthquake tomography and hypocenter relocation was performed using seismicity across Haiti from 2013–2014 Continued seismic activity was observed along Haiti's Southern Peninsula, associated with faults that ruptured during the Mw 7.0 2010 earthquake Hypocenters and a low velocity zone observed beneath the Massif de la Selle suggest a major south dipping thrust structure